PROBLEMS OF IMPLEMENTING THE CONSTITUTIONAL RIGHT TO HEALTH CARE IN THE REPUBLIC OF UZBEKISTAN - Komilova Muxtasar Abdunabi qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
Article 48 of our Constitution adopted on December 8, 1992 states that "Everyone has the right to use qualified medical services." This is the right of every citizen to receive free healthcare and medical care at state and city healthcare facilities at the expense of appropriate budget funds, insurance premiums and other income.